Barriers to dental providers’ use of a clinical decision support tool for pain management following tooth extractions - Shannon Gwin Mitchell; Jan Gryczynski; Donald C. Worley; Stephen E. Asche; Anjali R. Truitt; D. Brad Rindal (Implementation Research and Practice)
Background De-implementing non-effective or even harmful practices in healthcare is sometimes necessary, as has been the case with opioid prescribing in dentistry over the past decade. One approach to practice transformation is to deploy clinical decision support (CDS) tools. This qualitative study examined barriers to CDS use as part of a cluster randomized trial that aimed to decrease opioid prescribing for pain management following tooth extractions across a large dental practice. Method Twenty dental providers who took part in the larger randomized trial were purposively selected to complete a semi-structured qualitative interview. Participants represented a broad range in terms of years of practice, dental specialization, and CDS use patterns. Interviews were conducted via Zoom, audio recorded, transcribed, and analyzed using a content analysis approach in ATLAS.ti following participation in the cluster randomized trial. Results Reasons for not using the CDS fell generally into two broad categories: unintentional (i.e., forgetting to use the CDS) and intentional. Providers who forgot to use the CDS after training and implementation either were not sure where to look for the alert on the screen or did not remember to look for it because its use was never incorporated into their workflow. Reasons for deciding not to use the CDS included feeling that it slowed down their workflow, thinking that the information it provided would not be useful, and not trusting the functionality of the system. Conclusions There were numerous, interdependent human, organizational, and technological factors that influenced the intentionally and unintentionally low CDS use rates observed in the study. Findings highlight issues to be aware of and address in future implementation efforts that utilize CDS. Trial registration Clinicaltrials.gov NCT03584789.